Rebalancing cybersecurity imperatives: patching the social layer. Issue 1 (2nd January 2019) - Gioe, David V.; Goodman, Michael S.; Wanless, Alicia
ABSTRACT: The social layer, where civil society, including commercial and academic interaction, takes place is the most vulnerable one of the three commonly accepted layers of cyberspace. Worse still, emphasis by technical experts on physical and logical layer security has lulled civil society into a dangerous torpor that conflates information transmission reliability with reliable information. This has been exploited by criminals, adversarial states such as Russia and hostile non-state actors such as the Islamic State. This article explores the danger of an overly narrow conception of cybersecurity by governments and practitioners and recommends an urgent focus on the social layer toward a holistic rebalancing of cybersecurity. It offers a set of recommendations to help civil society secure itself in cyberspace.